<u>Answer:</u>
The amount lost over the 3 years s 2567.25£
<u>Explanation:</u>
![$\mathrm{F}=\mathrm{I} \times\left(1-\left(\frac{r}{100}\right)\right)^{\mathrm{n}}$](https://tex.z-dn.net/?f=%24%5Cmathrm%7BF%7D%3D%5Cmathrm%7BI%7D%20%5Ctimes%5Cleft%281-%5Cleft%28%5Cfrac%7Br%7D%7B100%7D%5Cright%29%5Cright%29%5E%7B%5Cmathrm%7Bn%7D%7D%24)
where F = final value after n years
I = initial value of the car in 2017 = £18000 (given)
Since the value is depreciated 5% every year for 3 years,
r = percentage rate of depreciation = 5% (given)
n = 3 years
Substituting these values in formula, we get
![$\mathrm{F}=18000 \times\left(1-\frac{5}{100}\right)^{3}$](https://tex.z-dn.net/?f=%24%5Cmathrm%7BF%7D%3D18000%20%5Ctimes%5Cleft%281-%5Cfrac%7B5%7D%7B100%7D%5Cright%29%5E%7B3%7D%24)
=
![$18000 \times\left(\frac{95}{100}\right)^{3}$](https://tex.z-dn.net/?f=%2418000%20%5Ctimes%5Cleft%28%5Cfrac%7B95%7D%7B100%7D%5Cright%29%5E%7B3%7D%24)
= 15432.75£ which is the value of the car after 3 years
Finally 18000-15432.75 = 2567.25£ is the amount lost over this period.
Let x be the distance (in feet) along the road that the car has traveled and h be the distance (in feet) between the car
and the observer.
(a) Before the car passes the observer, we have dh/dt < 0; after it passes, we have dh/dt > 0. So at the instant it passes the observer we have
dh/dt = 0, given that dh/dt varies continuously since the car travels at a constant velocity.
The expression x( x - 4 ) when expanded is x² - 4x
An expression, often known as a mathematical expression, is a finite collection of symbols that are well-formed in accordance with context-dependent principles.
When a bracket is expanded, each term is multiplied by the expression outside of the bracket.
The distributive property states that multiplying the sum of two or more addends by a number yields the same outcome as multiplying each addend separately by the number and combining the resulting products.
Consider the expression,
x( x - 4 )
Let us assume y = x( x - 4 )
Using the distributive property, a( b + c ) = ab + ac
y = x( x - 4 )
y = x · x - x · 4
y = x² - 4x
Therefore, x( x - 4 ) = x² - 4x
Therefore, the expression when expanded is x² - 4x.
Learn more about expression here:
brainly.com/question/1859113
#SPJ1
Answer:
um we need the photo sry
Step-by-step explanation:
One way of calculating the volume would be to convert all of these measurements to decimal:
V = (18 in)(30 in)(8 in) = 4320 cubic in